Tup1-Ssn6 and Swi-Snf remodelling activities influence long-range chromatin organization upstream of the yeast SUC2 gene - Fleming, Alastair B.; Pennings, Sari (Nucleic acids research, 2007)
The traditional model for chromatin remodelling during transcription has focused upon the remodelling of nucleosomes at gene promoters. However, in this study, we have determined that Tup1-Ssn6 and Swi-Snf chromatin remodelling activities extend far upstream of the SUC2 gene promoter into the intergenic region of the Saccharomyces cerevisiae chromosome. We mapped the nucleosomal array over a 7.5 kb region that encompassed the SUC2 gene promoter and upstream region but was devoid of other transcriptionally active genes. Nucleosome positioning over this region was determined under conditions of glucose repression and derepression, and in snf2, ssn6 and snf2 ssn6 mutant strains. A map detailing remodelling events extending as much as 5 kb upstream of the SUC2 gene promoter underlines the roles of the Tup1-Ssn6 and Swi-Snf complexes in respectively organizing and disrupting nucleosome arrays. The gene specificity of these events suggests a role in gene regulation. We propose that long-range chromatin remodelling activities of Swi-Snf and Tup1-Ssn6 may ultimately influence whether the chromosomal state of the SUC2 gene is proficient for transcription. These data raise the possibility that remodelling of extensive chromatin domains may be a general property of the Swi-Snf and Tup1-Ssn6 complexes.